Cell reaction of the primary teeth pulp after pulpotomy treatment with different medicines (LLC "Endo Press", 2020)
243 primary teeth in 112 children aged 3-8 years were treated using pulpotomy. The medicines «Pulpotek», «Trioxident» and «Viskosta» in combination with Zinkoxid Eugenol were used to cover the pulp stump. The reaction of immunocompetent cells of the teeth pulp to the above-mentioned medicines was studied in 48 teeth. 12 months later, after the treatment of pulpitis with Pulpotek and Viskostat combined with Zinkoxid Eugenol, the level IL 1β and TNF-α in the samples of the pulp tissue had no significant difference comparing with the normal index. There was no normalization of the pulp tissues in 33,3% of cases of pulpitis treatment with Trioxident that proved a decrease of the IL 1β level and an increase of that of TNF-α in the samples of the pulp tissues extracted after using this method